2012
DOI: 10.1111/j.1476-5381.2012.01894.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the hypothermic effects of imidazoline I2 receptor agonists in rats

Abstract: BACKGROUND AND PURPOSEImidazoline I2 receptors have been implicated in several CNS disorders. Although several I2 receptor agonists have been described, no simple and sensitive in vivo bioassay is available for studying I2 receptor ligands. This study examined I2 receptor agonist-induced hypothermia as a functional in vivo assay of I2 receptor agonism. EXPERIMENTAL APPROACHDifferent groups of rats were used to examine the effects of I2 receptor agonists on the rectal temperature and locomotion. The pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
72
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(79 citation statements)
references
References 46 publications
6
72
1
Order By: Relevance
“…Below: representative immunoblots for p-JNK and JNK in mouse HC after acute IR ligands. Note: efaroxan, moxonidine and idazoxan, but not LSL61122 (delayed hypothermic effects; seeThorn et al, 2012) significantly reduced the animal's rectal temperature at 60 minutes after administration (−1.1ºC to −1.7ºC, n=5; at least p<0.05); efaroxan, contrary to the data shown above, completely antagonised the moxonidine-induced hypothermia (p<0.05).…”
contrasting
confidence: 74%
See 1 more Smart Citation
“…Below: representative immunoblots for p-JNK and JNK in mouse HC after acute IR ligands. Note: efaroxan, moxonidine and idazoxan, but not LSL61122 (delayed hypothermic effects; seeThorn et al, 2012) significantly reduced the animal's rectal temperature at 60 minutes after administration (−1.1ºC to −1.7ºC, n=5; at least p<0.05); efaroxan, contrary to the data shown above, completely antagonised the moxonidine-induced hypothermia (p<0.05).…”
contrasting
confidence: 74%
“…Garau et al, 2013;Haxhiu et al, 1994;Kim et al, 2011;Sánchez-Blázquez et al, 2000;Thorn et al, 2012), and efaroxan (I 1 -IR) and idazoxan (I 2 -IR) as IR antagonists to prevent the effects of moxonidine and LSL61122, respectively (e.g. see Cambridge and Robinson, 2005;Haxhiu et al, 1994;Sánchez-Blázquez et al, 2000).…”
Section: Drugs and Reagentsmentioning
confidence: 99%
“…While some drugs, such as idazoxan (Sanchez-Blazquez et al, 2000; Thorn et al, 2012; Tonello et al, 2012) and BU224 (Sanchez-Blazquez et al, 2000; Bhalla et al, 2013) have been shown to attenuate the effects of I 2 receptor agonists such as 2-BFI and CR4056, those compounds have also been shown to have agonist effects in some assays, suggesting that they have low efficacy at I 2 receptors. For example, both 2-BFI and BU224 increase rotational behaviors in rats with nigrostriatal lesions (MacInnes and Duty, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although BU99006 binds selectively to I 2 receptors, its efficacy at these receptors has not been determined; however, to the extent that BU99006 has little or no efficacy, it might be a useful tool for selectively blocking other I 2 receptor ligands (Tyacke et al, 2002). This study examined the effects of BU99006, alone and in combination with I 2 receptor agonist 2-BFI, in two behavioral assays that are sensitive to I 2 receptor agonists, hypothermia and 2-BFI discrimination (Thorn et al, 2012; MacInnes and Handley, 2002). If BU99006 is an I 2 receptor antagonist, it is expected that it does not produce hypothermia or increase 2-BFI-associated lever responding as I 2 receptor agonists do (Thorn et al, 2012; MacInnes and Handley, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation